2006
DOI: 10.1159/000092460
|View full text |Cite
|
Sign up to set email alerts
|

3D-Ultrasound Detection of Fetal Grasping of the Umbilical Cord and Fetal Outcome

Abstract: A case of persistent fetal palmar grasping of the umbilical cord in a 23-year-old primigravida is described. Palmar grasping was detected with three-dimensional ultrasound examination after cardiotocographically recorded fetal bradyarrhythmia. Because of acute fetal hypoxia, urgent Misgav-Ladach cesarean section was performed to deliver a hypotrophic female newborn, 2,120 g/43 cm, Apgar score 4/7, pH 7.29. No other pathology was found during the procedure. The postoperative course proceeded uneventfully and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…An accurate antenatal diagnosis of umbilical cord abnormalities represents a significant challenge. Detection of nuchal cord or cord entanglement can be diagnosed by careful color Doppler studies and four-dimensional sonography [13]. Although nuchal cord detection with Doppler ultrasonography is easy, diagnosing cord entanglement around other parts of the body could sometimes be quite difficult.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate antenatal diagnosis of umbilical cord abnormalities represents a significant challenge. Detection of nuchal cord or cord entanglement can be diagnosed by careful color Doppler studies and four-dimensional sonography [13]. Although nuchal cord detection with Doppler ultrasonography is easy, diagnosing cord entanglement around other parts of the body could sometimes be quite difficult.…”
Section: Discussionmentioning
confidence: 99%
“…2), manipulate, and even squeeze the umbilical cord. Partial or intermittent complete cord occlusion alters the blood flow in the umbilical cord, increases the afterload, and decreases (Ball and Parer 1992), which results in increased vagal activity causing variable fetal heart rate decelerations by up to 15-60 beats per minute (Petrikovsky and Kaplan 1993;Habek et al 2006). Such a significant heart rate deceleration may result in diminished fetal cardiac output due to a poorly developed Frank-Starling mechanism at low fetal heart rates.…”
Section: Arm Hand and Finger Movementsmentioning
confidence: 99%
“…[31][32][33] One report describes the 3DUS detection of umbilical cord compression by fetal grasping with good fetal outcome. 34 In addition, evaluation of nuchal cord at birth has been evaluated with 3DUS and compared to 2DUS findings by Hanaoka et al: 35 the authors concluded that 3DUS imaging did not provide more useful diagnostic information compared with two-dimensional and colour Doppler ultrasound for detecting nuchal cord in utero. However, better visualization of the nuchal umbilical cord by 3DUS was reported subjectively by the sonographers.…”
Section: Umbilical Cordmentioning
confidence: 99%